DUKUNGAN ORANG TUA TERHADAP KETERLIBATAN ANAK BERMAIN DI KAMPOENG DOLANAN KELURAHAN SIMOKERTO KOTA SURABAYA - Mahdalena Putri, Ayunda; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2025)
Children's dependence on online games occurs in Simokerto Village, Surabaya City, even though it has many negative impacts. This makes parents try to free their children from online games by utilizing the existence of Kampoeng Dolanan. The purpose of this research is to reveal the reasons why parents in Simokerto Village provide support and describe the form of parental support for children's involvement in playing in Kampoeng Dolanan. The theory used is the Social Support Theory from James S. House. This research uses a qualitative method with a case study design. The focus of the research is the reasons and forms of parental support in Simokerto Village for children to play in Kampoeng Dolanan. Data collection used moderate participant observation and in-depth interviews. The data analysis technique used qualitative analysis from Miles and Huberman. The results of the research showed that there were three reasons why parents provided support for children to play in Kampoeng Dolanan, namely: (1) diverting children's attention from gadgets; (2) forming social skills; (3) introducing children to traditional games. The results of the research also showed that there were various forms of parental support in Simokerto Village which could be grouped according to James S. House's Social Support Theory. First, emotional support was found when parents gave permission and ordered children to play in Kampoeng Dolanan. Second, instrumental support was found when parents gave pocket money, transportation, accompanied, and supervised children playing. Third, information support was found when parents taught how to play traditional games and gave advice. Fourth, appreciation support was found when parents gave praise after children played in Kampoeng Dolanan. Based on the results of the research, it was found that the diversity of forms of parental support could be due to busyness and distance from home.